Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Could you please explain how come: $$\sum_{i=1}^\infty(0.5)^{i+1}(i+1)=2$$

How come the answer is not inf? And why 2?

Any help will be appreciated.

share|cite|improve this question
See this similar question for ideas. – David Mitra Apr 19 '13 at 11:55
up vote 2 down vote accepted

We know for $|r|<1$, $$\sum_{1\le i<\infty}r^{i+1}=r^2\cdot\frac1{1-r}=\frac{r^2}{1-r}$$

$$\text{Now, }\frac{d\left(\sum_{1\le i<\infty}r^{i+1}\right)}{dr}=\sum_{1\le i<\infty}\frac{d r^{i+1}}{dr}=\sum_{1\le i<\infty}(i+1)r^i$$

$$\text{and }\frac{d\left(\frac{r^2}{1-r}\right)}{dr}=\frac{2r-r^2}{(1-r)^2}$$

$$\implies \sum_{1\le i<\infty}(i+1)r^i=\frac{2r-r^2}{(1-r)^2}$$

$$\implies \sum_{1\le i<\infty}(i+1)r^{i+1}=\frac{r(2r-r^2)}{(1-r)^2}$$

Alternatively, using Arithmetico-geometric series, we can show, $$\sum_{1\le i<\infty}(i+c)r^{i+1}=\frac{(c+1)r^2-c\cdot r^3}{(1-r)^2}$$ where $c$ is any finite number

Let $S=\sum_{1\le i<\infty}(i+c)r^{i+1}$

Multiply either sides by the common ratio $r,$ and subtract from the original

share|cite|improve this answer
I'm not sure what you did here and why. Can you please explain? – Manko Apr 19 '13 at 11:31
@Mankochka, do you know Infinite Geometric Series ( with common ratio=$r$? If yes, the apply derivative wrt $r$ – lab bhattacharjee Apr 19 '13 at 11:37
I understood the proof you linked to, but as it doesn't mention derivatives I don't understand how to apply it to my example, and what are the steps you performed. – Manko Apr 19 '13 at 13:02
@Mankochka, please find the edited answer – lab bhattacharjee Apr 19 '13 at 16:02
Finally got it, thanks :) – Manko Apr 19 '13 at 16:34

You wonder why the sum

$$\sum_{k=2}^{\infty} k \left ( \frac{1}{2}\right)^k$$

does not blow up, presumably because of the factor of $k$ in the sum which grows linearly to $\infty$. The answer, very roughly, is because the factor of $(1/2)^k$ decreases much more quickly than $k$ increases.

Let's look at a few terms to see how this works. The first few terms in the sum look like

$$2 \left( \frac{1}{2}\right)^2 + 3 \left( \frac{1}{2}\right)^3 + 4 \left( \frac{1}{2}\right)^4 + \ldots = \frac{2}{4} + \frac{3}{8} + \frac{4}{16}+ \ldots$$

The terms here are already getting smaller at $k=2$. Now let's double the index:


You should see that, while the numerator doubles, i.e., exponent increases by $1$, the denominator is squared, i.e., exponent is doubled.

I hope you see that the terms in the series rapidly vanish as $k \rightarrow \infty$. By comparison with far more slowly varying sequences whose corresponding series converge (e.g., $1/k^2$), this series converges.

It converges to $3/2$ for reasons summarized by @lab above.

share|cite|improve this answer
I wish I could accept both answers, thanks :) – Manko Apr 19 '13 at 16:35

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.